2015
DOI: 10.1371/journal.pone.0139549
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis of Abdominal Fat in Genetically Fat and Lean Chickens Highlights a Divergence in Expression of Genes Controlling Adiposity, Hemostasis, and Lipid Metabolism

Abstract: Genetic selection for enhanced growth rate in meat-type chickens (Gallus domesticus) is usually accompanied by excessive adiposity, which has negative impacts on both feed efficiency and carcass quality. Enhanced visceral fatness and several unique features of avian metabolism (i.e., fasting hyperglycemia and insulin insensitivity) mimic overt symptoms of obesity and related metabolic disorders in humans. Elucidation of the genetic and endocrine factors that contribute to excessive visceral fatness in chickens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 132 publications
3
64
0
Order By: Relevance
“…Native PLIN1 may serve as a barrier, protecting droplet triglycerides from basal lipolysis, whereas phosphorylated PLIN1 could indirectly activate ATGL [36,37]. Previous studies have found that the expression of PLIN1 was higher in muscles with high IMF contents [34,38]. In addition, AFABP, a negative regulator of mitochondrial fatty acid oxidation [39], was also upregulated in the F line.…”
Section: Ppar Pathway Regulates Weakened Lipolysis and Enhanced Lipogmentioning
confidence: 96%
“…Native PLIN1 may serve as a barrier, protecting droplet triglycerides from basal lipolysis, whereas phosphorylated PLIN1 could indirectly activate ATGL [36,37]. Previous studies have found that the expression of PLIN1 was higher in muscles with high IMF contents [34,38]. In addition, AFABP, a negative regulator of mitochondrial fatty acid oxidation [39], was also upregulated in the F line.…”
Section: Ppar Pathway Regulates Weakened Lipolysis and Enhanced Lipogmentioning
confidence: 96%
“…The priority of abdominal fat tissue in broiler chickens to identify genes involved in metabolism and fat storage is due to the fact that it can be as a prior model in other species and individuals of a species due to its speci c metabolic characteristics [38]. The present study detected a total of 34 common genes that played roles in the main process of synthesis route control, metabolism and fat storage, and signaling pathways of endocrine glands activated by adipokines, AMPK and PPAR.…”
Section: Discussionmentioning
confidence: 78%
“…In the last 60 years, the selection of important economic traits has been the focus and significant genetic improvements have been gained(Dong et al, 2015). Genetic selection for enhanced growth rate in meat-type chickens (Gallus domesticus) is usually accompanied by excessive adiposity, which has negative impacts on both feed efficiency and carcass quality(Resnyk et al, 2015). The genetic improvement of abdominal fat by standard selection has been lower for two reasons: (1) intensity of selection has been lower because of the difficulty and cost to measure these phenotypes, and (2) genetic evaluations have been less accurate because evaluation of candidates is based on information from relatives only(Demeure et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the molecular regulation mechanisms of fat deposition in broilers is helpful for optimal breeding. Many studies have been carried out on gene expression of chicken abdominal fat using genome-wide RNA sequence(Resnyk et al, 2013; Resnyk et al, 2015; Zhuo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%